Weed mangement Elucidating the impact of new-generation herbicides on productivity and phytotoxicity on chickpea (Cicer arietinum) and their residual effects - SHEKHAWAT, KAPILA; SANKETH, G D; REKHA, K BHANU; CHAITHANYA, Y; PRAKASH, T RAM; SUDHAKAR, K S (The Indian Journal of Agricultural Sciences, 2023)
The study suggests that in chickpea higher WCI, HEI and lower WI were noticed with the application of pendimethalin + imazethapyr 1.0 kg/ha as PE fb MW at 30 DAS. Although the application of topramezone @25.2 g/ha as PoE fb MW at 40 DAS (T5) resulted in higher WCI and lesser weed dry weight at both 60 and 90 DAS, the residual effect of this treatment was evident on the succeeding crops. Thus, standardization of the dose of topramezone for chickpea without any phytotoxic effect on the succeeding crops would pave the way for effective weed management in a cropping system mode.